Gaming Democracy: How Silicon Valley Leveled Up the Far Right by Adrienne L. Massanari (The MIT Press, 2024): Book review - Condis, Megan (Eludamos: Journal for Computer Game Culture, 2025)
A Review of Adrienne L. Massanari’s Gaming Democracy: How Silicon Valley Leveled Up the Far Right. Published by The MIT Press, 2024. ISBN: 9780262380331, 238 pages.